Ciudadanos en la red: facebook y opinión sobre las corridas de toros - Tamayo Molina, Liz Johann; Villa Zapata, Ana María (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This article discusses the public opinion polemicsabout bullfight followers and its detractors in the virtual social web Facebook and in general studies the characteristics of participation in Internet.It also presents an overview of the relation between democracy, par-ticipation and communication when dialogue is mediated by digital technologies of information and communication.